KAJIAN TEKNO EKONOMI UNIT ALAT PENCACAH PLASTIK UNTUK MENINGKATKAN NILAI JUAL SAMPAH PLASTIK: STUDI KASUS-UD. SARI PLASTIK LOMBOK TIMUR, NTB - I Made Suartika; Made Wijana; Muhamad Sudrajadinata (Dinamika Teknik Mesin, 2015)
Processing plastic waste in East Lombok mostly just collect plastic waste processing and then sent to the city in its original form. If the plastic waste is processed by applying plastic shredded units or chopper machine technology, the sale value of the plastic waste will be increased. This study describes to determine of feasibility technical and economic aspects to apply the plastic shredder units. The method used in this study is quantitative method in which the author will be a number of data collection is needed in relation to the issues to be examined, so that the research results can be trusted and relied upon the truth. The results of the study found that the engine performance in terms of the efficiency of each stage of the production process of shredded plastic. To purchase process stages, sorting, drying, packaging, and selling obtained an efficiency of 0.938, while the efficiency of the shredding process is 0.906. Furthermore, to obtain a production capacity of 1230.01 kg/day processing owners must buy raw materials 1588.34 kg/day by the number of machines required 2 units of 3 units of existing plastic shredder. So based on the feasibility analysis in terms of the value of BEP, obtained at 29092.03 kilogram production capacity, with a total cost of Rp 176,424,168.75, NPV Rp 113,545,038.34 (>0) and Net B/C ratio of 1.79 (>0) otherwise feasible. By optimizing the engine to 3 units obtained BEP value equal to the NPV Rp 385.139.485,25 (>0) and Net B/C ratio of 4.01 (>0). From the analysis of the value of shredded plastic BEP selling price is higher than the selling price of plastic intact from Rp 3,531/kg into Rp 6.064,35/kg.